Primary Tr1 cells from metastatic melanoma eliminate tumor-promoting macrophages through granzyme B- and perforin-dependent mechanisms - Hongxia Yan; Ping Zhang; Xue Kong; Xianglian Hou; Li Zhao; Tianhang Li; Xiaozhou Yuan; Hongjun Fu (Tumor Biology)
In malignant melanoma, tumor-associated macrophages play multiple roles in promoting tumor growth, such as inducing the transformation of melanocytes under ultraviolet irradiation, increasing angiogenesis in melanomas, and suppressing antitumor immunity. Because granzyme B- and perforin-expressing Tr1 cells could specifically eliminate antigen-presenting cells of myeloid origin, we examined whether Tr1 cells in melanoma could eliminate tumor-promoting macrophages and how the interaction between Tr1 cells and macrophages could affect the growth of melanoma cells. Tr1 cells were characterized by high interleukin 10 secretion and low Foxp3 expression and were enriched in the CD4 + CD49b + LAG-3 + T-cell fraction. Macrophages derived from peripheral blood monocytes in the presence of modified melanoma-conditioned media demonstrated tumor-promoting capacity, exemplified by improving the proliferation of cocultured A375 malignant melanoma cells. But when primary Tr1 cells were present in the macrophage-A375 coculture, the growth of A375 cells was abrogated. The conventional CD25 + Treg cells, however, were unable to inhibit macrophage-mediated increase in tumor cell growth. Further analyses showed that Tr1 cells did not directly eliminate A375 cells, but mediated the killing of tumor-promoting macrophages through the secretion of granzyme B and perforin. The tumor-infiltrating interleukin 10 + Foxp3 − CD4 + T cells expressed very low levels of granzyme B and perforin, possibly suggested the downregulation of Tr1 cytotoxic capacity in melanoma tumors. Together, these data demonstrated an antitumor function of Tr1 cells through the elimination of tumor-promoting macrophages, which was not shared by conventional Tregs.